Assessing climate change impacts on wind characteristics in Greece through high resolution regional climate modelling. (December 2021) - Katopodis, Theodoros; Markantonis, Iason; Vlachogiannis, Diamando; Politi, Nadia; Sfetsos, Athanasios
Abstract: This work introduces an assessment of the projected climatic changes in wind characteristics in Greece through the WRF model 5 × 5 km 2, forced by the EC-EARTH Global Climate Model (GCM). Firstly, the model is validated against historic observations at 10 m, before being applied to the Representative Concentration Pathways (RCPs) 4.5 and 8.5 that represent an average expected future and a worst-case scenario. Projected changes in the mean annual wind speed at 100 m, between the historic (1980–2004) and future (2020–2044) scenarios are found to vary locally between −5% and +20%, whereas for the Wind Energy Density (WED) this variation lies between −15% and +60%. Overall, robust and significant increases regarding the mean wind speeds were found mainly over the north and central-western Aegean region, the Island of Crete, as well over Greek mainland and the Ionian Sea. Both scenarios predicted higher statistically significant increases in the Weibull shape parameter values (of about 0.2) in the north–central Aegean, while the summer seasonal analysis, yielded significant decreases over the western Ionian Sea and south and south-western parts of Crete, which might be indicative of more gusty events. Finally, extreme wind speeds analysis indicated increases, which might affect wind turbines structural integrity. Highlights: Future indicated negative trend in most parts of the Aegean Sea and continental Greece. RCP 4.5 scenario indicated increases in the summer for the v100 (2.0–2.5 m/s). RCP4.5 estimated increases over mountains, Crete and the Aegean Sea up to 350 W/m 2 . Maximum wind speeds over 40 m/s are expected in the southern parts of Crete. RCP 8.5 yielded further decreases (−0.02 to −0.03 m/s) compared to RCP 4.5 in the u∗.